Pathogenic paternally inherited NLGN4X deletion in a female with autism spectrum disorder: Clinical, cytogenetic, and molecular characterization. Issue 3 (24th December 2020) - Kopp, Nathan; Amarillo, Ina; Martinez‐Agosto, Julian; Quintero‐Rivera, Fabiola
Abstract: Neuroligin 4 X‐linked ( NLGN4X ) is an X‐linked postsynaptic scaffolding protein, with functional role in excitatory synapsis development and maintenance, that has been associated with neuropsychiatric disorders such as intellectual disability, autism spectrum disorders (ASD), anxiety, attention deficit hyperactivity disorder (ADHD), and Tourette's syndrome. Chromosomal microarray analysis identified a paternally inherited, 445 Kb deletion on Xp22.3 that includes the entire NLGN4X in a 2.5 year old female (46, XX) with congenital hypotonia, strabismus, ASD, and increased aggressive behavioral issues. Her family history is significant for a mother with learning disabilities, a father with anxiety, major depressive disorder, and substance abuse, as well as two maternal half‐brothers with developmental delays. X‐inactivation studies in the proband's blood showed random X‐inactivation despite the presence of an abnormal X chromosome. Furthermore, trio exome sequencing did not reveal any other deleterious variant that could explain her phenotype. Our report describes the first example of a paternally inherited NLGN4X microdeletion as the genetic etiology of ASD in a female proband, and the psychiatric phenotypes in the father. It also provides further evidence that NLGN4X is sensitive to dosage changes in females, and can contribute to a variety of psychiatric features within the same family.